ADMINISTRATIVE DISCRIPTION: REFLECTIONS ON JUDICIAL INTERVENTION IN POLICY APPOINTIMENTS OF EXECUTIVE POWER (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article aims to examine judicial intervention in typical powers of the Executive Branch, making the political discretion of the President of the Republic questionable in the face of repeated and conflicting decisions by the Judiciary Branch. To illustrate the theme, the following nominations were analyzed by the Supreme Federal Court: the ex-president Luiz Inácio Lula da Silva as Minister of the Civil House (MC in MS 34.070-DF); Cristiane Brasil, before the role of Minister of Labor, (MC in Rcl 29.508 / DF) and Eduardo Bolsonaro as Ambassador to the United States of America (MS 36.620 / DF). We sought to establish the boundaries between the necessary judicial action to correct abuses and illegalities versus the adoption of moral corrections (judicial politicization) arising from activist manifestations by the Judiciary. It concludes, in general, by the excessive interference of the STF in typical acts of the Executive Power, whose legality decays before moral and political judgments unfit to be sustained in constitutional hermeneutics.